2013
DOI: 10.1177/193758671300701s04
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Facility Design in Preventing the Transmission of Healthcare-Associated Infections: Background and Conceptual Framework

Abstract: To describe the conceptual framework and methodology used to conduct a comprehensive literature review of current evidence evaluating the role of the built environment in the transmission of healthcare-associated infections. BACKGROUND: A multidisciplinary approach to evaluating a vast and diverse dataset requires a conceptual framework to create a common understanding for interpretation. This common understanding is accomplished through the application of a "chain of transmission" model, depicting temporal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…Esse resultado ratifica o que afirmaram os estudos sobre a existência de um crescente corpo de evidências sugerindo que o ambiente construído é importante na prevenção da transmissão de agentes patogênicos, e que soluções de projeto podem reduzir o risco de infecções (24,25,26). Contudo, é evidente que outros aspectos não abarcados pela Arquitetura, como as práticas da ES, seguem como fatores fundamentais nesse processo.…”
Section: Resultados E Discussõesunclassified
“…Esse resultado ratifica o que afirmaram os estudos sobre a existência de um crescente corpo de evidências sugerindo que o ambiente construído é importante na prevenção da transmissão de agentes patogênicos, e que soluções de projeto podem reduzir o risco de infecções (24,25,26). Contudo, é evidente que outros aspectos não abarcados pela Arquitetura, como as práticas da ES, seguem como fatores fundamentais nesse processo.…”
Section: Resultados E Discussõesunclassified
“…When proposing the solutions for all the issues, the HF layout and the department configuration was seen to be a contributive parameter. Significant evidence indicated that the HF plan layout was a major contributing factor which increases the NI transmission, and interventions related to the HF environment could mitigate the infection risk [7,79,80]. Currently, consent for controlling the infections is considered an important parameter which could improve the planning, construction, and the operations of the HFs [81].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation units for airborne infections should be safe enough for high-risk cases, if used properly [1,9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. There should be no offices, laboratories, other patient wards or other regular human activities under, over or around this isolation unit.…”
Section: Strict Isolation Unitmentioning
confidence: 99%